2017
DOI: 10.1002/jca.21535
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic plasma exchange versus double plasma molecular absorption system in hepatitis B virus‐infected acute‐on‐chronic liver failure treated by entercavir: A prospective study

Abstract: Compared to DPMAS, TPE was more efficient in eliminating TBIL, DBIL, and hsCRP, but it was associated with higher loss rate of albumin. TPE and DPMAS were similar in improving 12-week survivals in HBV-ACLF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 35 publications
(67 reference statements)
0
45
1
Order By: Relevance
“…Appropriate statistical methods are also important for assessing the effects of ALSS treatment in patients with HBV‐ACLF. A few single‐center studies with limited samples have reported the beneficial effect of ALSS on survival in patients with HBV‐ACLF 14,15,25 . In the present multicenter and large cohort study, we used multiple adjusted methods, including multivariable risk adjustment, case‐control matching, PSM, and IPTW analysis, to reduce the bias 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Appropriate statistical methods are also important for assessing the effects of ALSS treatment in patients with HBV‐ACLF. A few single‐center studies with limited samples have reported the beneficial effect of ALSS on survival in patients with HBV‐ACLF 14,15,25 . In the present multicenter and large cohort study, we used multiple adjusted methods, including multivariable risk adjustment, case‐control matching, PSM, and IPTW analysis, to reduce the bias 29 .…”
Section: Discussionmentioning
confidence: 99%
“…All patients took daily entecavir (0.5 mg/day) or tenofovir (300 mg/day) once they were tested positive for HBV-DNA throughout the study period. Most patients also underwent artificial liver support (ALS) treatment by therapeutic plasma exchange (TPE) and/or double plasma molecular absorption system (DPMAS) as described in previous studies 20 , 21 . During the hospitalization period, all patients received standard medical treatment, including intravenous reduced glutathione, polyene phosphatidylcholine, glycyrrhizin, and ademetionine.…”
Section: Methodsmentioning
confidence: 99%
“…In ACLF, there are two single-center, non-controlled observational studies [137,138] and two randomized controlled trials evaluating the plasma-exchange either against the molecular adsorbent system (non-MARS) [139] or standard of care [140]. Results suggest its feasibility and a positive effect on the survival.…”
Section: Extracorporeal Devicesmentioning
confidence: 99%